Present and future of criminal mediation in Spanish law: is a higher degree of uncertainty even possible? - José Francisco Etxeberria Guridi (Revista Brasileira de Direito Processual Penal, 2019)
The main aim of this paper is to analyze the procedural issues that arise in the implementation of the criminal mediation. The benefits of criminal mediation and restorative justice are unquestionable. Nevertheless, in the Spanish legal system there are no satisfactory statutory provisions to answer decisive questions, such as the kinds of crimes can be diverted to mediation, the competent authority to adopt this decision, the procedural phase in which the mediation should take place or the way to incorporate the results of the mediation process in the judicial proceedings. The aforementioned uncertainty whiting the Spanish legal system is difficult to understand considering that Directive 2012/29/UE on the protections of victims of crime has been transposed into the Spanish legal system (Act 4/2015) and taking into account that two comprehensive proposals to reform the Spanish criminal proceedings have been published, in which the questions above had been solved.